ZEOLITE PROCESSING AS HEAVY MATERIAL - Dur, Sajaratud (ZERO: Jurnal Sains, Matematika dan Terapan, 2017)
Research on zeolite processing as a reinforcement material is done to utilize natural resources in North Sumatera Province. Zeolite processing is so nanometer-sized by using a ballmill. Activation of zeolite is done by heating 1050 C for 10 minutes. The resulting zeolite particle size is 290 nanometers. It is obtained from 80 grams of zeolite measuring 1700 nanometers to 15 grams measuring 290 nanometers for 34 hours of grinding process in the ballmill.